Federalism within a unitary state: Institutional dynamics of BARMM and conflict resolution in the Philippines - Maftuhatul Choiroh; Honest Dody Molasy; Adhiningasih Prabhawati (Priviet Social Sciences Journal, 2026)
The conflict between the Philippine government and the Muslim community in Mindanao stems from historical marginalization, ongoing violence, and the rejection of previous attempts to grant autonomy by various groups. This study analyzes the establishment of the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM) through the Bangsamoro Organic Law (BOL) of 2019. By positioning BARMM as a form of constitutional asymmetry within the framework of the unitary state of the Philippines, this study highlights how BARMM operates as a federal dynamic that balances self-rule and shared rule without fully adopting a federal system. Using qualitative descriptive research, this study demonstrates that BARMM strengthens national integration through (1) constitutional asymmetry as an instrument for managing diversity, (2) the implementation of BARMM: self-rule and shared rule, (3) political legitimacy through symbolic and functional reconciliation, and (4) the need to mitigate structural challenges and risks within BARMM. This study concludes that constitutional asymmetry functions as a strategic mechanism in the construction of peace from within and provides an analytical paradigm to explain ethnopolitical diversity within the socio-political structure of the society.